Upaya Mewujudkan “Merdeka Belajar” melalui Manajemen Kurikulum di MA Miftahul Ulum untuk Meningkatkan Mutu Pendidikan - Abdurrahman, Abdurrahman; Hidayatullah, Moh. Yoga; Farizi, Salman; Humaidi, Muhammad (Universitas Nurul Jadid, 2025)
The realisation of ‘Merdeka Belajar’ in madrasah is one of the important programmes in improving existential and sustainable education services. Various efforts have been made by the government, such as the implementation of Merdeka Belajar as stated in the Ministry of Education and Culture Decree No. 56 of 2022. This research was conducted at MA Miftahul Ulum Krucil Probolinggo with the aim of: 1) describe the procedural and conceptual models of Merdeka Belajar Management to realise ‘Merdeka Belajar’; 2) describe the results of implementing Merdeka Belajar Management to realise ‘Merdeka Belajar’. The method used in this research is a qualitative study, data collection techniques through observation, interviews, and documentation. The results showed that the implementation of Merdeka Curriculum to realise Merdeka Belajar at MA Miftahul Ulum to improve the quality of education by collaborating with various stakeholders, both teachers and students and between teachers. The collaboration technique used is to use the Top Down and Bottom Up patterns, namely breaking down from AKUL (Institutional Curriculum Direction) into programmes from the madrasah and involving regulations from the Ministry of Education and Culture.